Polycrystalline Gan Layer On M-Plane Sapphire Substrate For Metal-Semiconductor-Metal Photodetector - Kamarulzaman, Azharul Ariff (2017)
This thesis describes work on depositing polycrystalline gallium nitride (GaN) on m-plane sapphire substrate using cost effective physical deposition technique; electron beam (e-beam) evaporator and radio frequency (RF) sputtering, followed by annealing treatment in ammonia (NH3) ambient. The work was then extended to develop metal-semiconductor-metal (MSM) photodetector using the most possible metal/metal oxide contact, to increase the efficiency of the device. The initial part of this thesis focus on ameliorating the properties of the polycrystalline GaN layer by controlling gas ambient, time, temperature, and gas flow rate of the annealing treatment.